2002
DOI: 10.1086/324277
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Depletion in Pre–Main‐Sequence Solar‐like Stars

Abstract: We examine the internal structure of solar-like stars in detail between 0.8 and 1. 4 and during M _ preÈmain-sequence phase. Recent opacity computations of OPAL along with a new hydrodynamical mixing process have been considered. We also introduce up-to-date nuclear reaction rates and explore the impact of accretion, mixing length parameter, nonsolar distributions among metals, and realistic rotation history. Models predict lithium depletion that we compare to the 7Li content observations of the Sun and four… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 72 publications
8
129
1
Order By: Relevance
“…Two hypotheses can be proposed to explain the difference between the abundances that we have derived for our sample stars and the meteoritic Be abundance: a) All our sample stars, including the young cluster star, have undergone a very similar amount of Be depletion; b) The difference between our best fit Be abundances and the meteoritic value is simply due to different analytical methods adopted during the analyses. Under this hypothesis, none of our sample stars has undergone any Be depletion, implying that stars in this temperature range including the Sun, do not burn Be while on the MS. Hypothesis a) would mean that some Be burning occurs during the pre-main sequence (PMS) phases, in contradiction with all model predictions (e.g., Piau & Turck-Chieze 2002) and inconsistently with the observational evidence of no PMS Li depletion for stars in this T eff range (e.g., Randich et al 2001 and references therein); in other words, the simultaneous Be depletion and Li non-depletion in the young star would be hardly explainable. For these reasons, we regard hypothesis a) as very unlikely.…”
Section: Be and LI Abundancesmentioning
confidence: 81%
“…Two hypotheses can be proposed to explain the difference between the abundances that we have derived for our sample stars and the meteoritic Be abundance: a) All our sample stars, including the young cluster star, have undergone a very similar amount of Be depletion; b) The difference between our best fit Be abundances and the meteoritic value is simply due to different analytical methods adopted during the analyses. Under this hypothesis, none of our sample stars has undergone any Be depletion, implying that stars in this temperature range including the Sun, do not burn Be while on the MS. Hypothesis a) would mean that some Be burning occurs during the pre-main sequence (PMS) phases, in contradiction with all model predictions (e.g., Piau & Turck-Chieze 2002) and inconsistently with the observational evidence of no PMS Li depletion for stars in this T eff range (e.g., Randich et al 2001 and references therein); in other words, the simultaneous Be depletion and Li non-depletion in the young star would be hardly explainable. For these reasons, we regard hypothesis a) as very unlikely.…”
Section: Be and LI Abundancesmentioning
confidence: 81%
“…At this age, the star is located at the turning point of the PMS evolutionary track, just after the Hayashi descent. Its radiative core is developing quickly, and there is strong lithium burning (Piau & Turck-Chièze 2002, Fig. 1).…”
Section: Setting the Young Sun Modelmentioning
confidence: 99%
“…Piau & Turck-Chièze (2002) have shown that 7 Li burning depends strongly on many ingredients during its short phase of burningtypically from 2 to 10 Myr for young suns-which corresponds to the contraction phase and a large increase of the temperature and density at the base of the convective zone. Models of solarlike stars show a stronger depletion of lithium than the observed ones (Ventura et al 1998;Piau & Turck-Chièze 2002), with a great dependence on the internal composition (see also Sestito et al 2006) and on dynamical processes. The convective zone is clearly a crucial element and many questions have been addressed on the role of magnetic field on its extension and also of the effects of turbulence in this region.…”
Section: Introductionmentioning
confidence: 99%
“…This mixing is also influenced by differential rotation (Zahn 1983;Lebreton & Maeder 1987;Brun et al 1999) and magnetic field (McIntyre 2007). Additional lithium depletion can also be caused by other mechanisms such as stellar wind (Vauclair & Charbonnel 1995;Morel et al 1997), circumstellar disks at the early stage of evolution (Piau & Turck-Chièze 2002) as well as activity during the early MS lifetime (Turck-Chièze et al 2011).…”
Section: Introductionmentioning
confidence: 99%